Determination of susceptibility levels of three different cockroach species including hospitals German cockroach, Blattella germanica L. (Blattodea: Blattellidae), to common insecticides, cypermethrin, propoxur and fenitrothion - Fazeli-Dinan, Mahmoud; Habibi, Aliasghar; Motevalli Haghi, Seyed Farzad; Nikookar, Seyed Hassan; Yazdani-Charati, Jamshid; Enayati, Ahmadali (International Journal of Health Sciences, 2022)
Objective: German cockroach is highly adapted to different environments like hospitals. This pest is an important carrier of pathogenic agents and allergic compounds. Hence, it is important to German cockroaches always be monitored and controlled. This study investigated the toxicity and resistance levels of technical-grade of cypermethrin, propoxur, and fenitrothion against adult males of four strains of the German cockroach. Methods: Four German cockroaches’ strains including laboratory-reared susceptible strain (S) and three hospital-collected strains (B, F, and Z) were tested in this study. Adult male cockroaches were treated topically with three technical grade insecticides on the first abdominal segment of the insects using a hand micro-applicator. Results: Using topical application methods, fenitrothion showed the most toxicity to all four strains. The LD50 values of fenitrothion in the susceptible strain (S) and the hospital-collected strains B, F, and Z were 1.89, 21.48, 25.73, and 31.55 μg/grBW, respectively. All hospital-collected strains showed different resistant levels to all insecticides. The field-collected Z strain was the most resistant strain to cypermethrin, propoxur, and fenitrothion. The resistance ratios of strain Z to cypermethrin, propoxur, and fenitrothion were 10.9, 10.47 and 16.67, respectively. Conclusion: Based on the susceptibility and resistance ratios for each insecticide, we conclude that there are high rates of insecticide resistance in Blattella germanica from different hospitals of Sari County which can be caused by different insecticides treatment histories.